Some considerations about the contribution of roller shutters positions to noise insulation of façades - Patrício, Jorge (2004)
This paper describes an experimental study on the evaluation of the influence of roller shutters positions on noise insulation of façades. The study is based on the results of a set of tests carried out in laboratory, and in situ using the 1st, 2nd, 3rd and 4th floors of a selected new housing building which is typical of Portuguese cooperative construction. For the purpose a specific type of window was considered. The window system (glazing and frame, plus the roller shutter) was firstly characterized in laboratory. In situ, the tests were performed in 2 different rooms having different window dimensions. The measurements were done in accordance with what is prescribed by international standards, using a loudspeaker as noise source. The considered shutters positions were: totally opened, half closed, partially closed (shutter extended) and completely closed (shutter fully extended). Additionally, in situ measurements with the window open were also done. The results have shown that the façade transmission loss curve related to each shutter position at the same storey and between different floor levels differs with some significance. Other interesting and important conclusions were extracted from the study done, namely: i) the important influence of shutter position when the window is open; the discrepancy between laboratory and in situ sound insulation performance; the low influence of flanking transmission regarding façades performance, which is due to its weak sound insulation when compared to those of the adjoining elements; and, finally, the evolution of sound insulation in frequency domain for the set of combinations window open and closed versus shutter positions.